"Using a Spoon to Claw Your Way Out of a Steel Cage": A Candidate Works with the Frustration and Defeatism of a College Student with Inattentive ADHD and Depression. Issue 1 (1st January 2019) - Whitman, Laura
ABSTRACT: Mark, a college student with attention deficit disorder, depression, and a language-based learning disability, was seen in psychoanalysis. The analytic work included defense interpretation, elucidation of unconscious themes, and construction of a life narrative. The treatment was multimodal, as is common in working with adolescents and emerging adults with learning disabilities and attention deficit disorder. The analyst prescribed stimulants and antidepressants, and referred the patient for psychological testing, tutoring, and educational accommodations. Understanding the shame associated with learning difficulties was crucial to the patient's progress. This case report describes the beginning phase of a psychoanalytic treatment. Early transference, in the sense of reviving old objects, included feelings of mistrust and projection of harsh self-judgment. Gradually, the patient developed a reciprocal and collaborative partnership with the analyst that represented features of the real relationship, wherein Mark could internalize aspects of her that were more caring and compassionate than his own attitude toward himself (Abrams, Neubauer, and Solnit 1999). The patient developed the ability to observe himself, to recognize unconscious determinants of his behavior and to make use of the experience of transference.